2009
DOI: 10.1016/j.nic.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy in Multiple Sclerosis

Abstract: Synopsis Proton magnetic resonance spectroscopy (1H-MRS) provides tissue metabolic information in vivo. This article reviews the role of MRS-determined metabolic alterations in lesions, normal appearing white matter, gray matter, and spinal cord in advancing our knowledge of pathological changes in multiple sclerosis (MS). In addition, the role of MRS in objectively evaluating therapeutic efficacy is reviewed. This potential metabolic information makes MRS a unique tool to follow MS disease evolution, understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
111
1
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 116 publications
(147 reference statements)
3
111
1
10
Order By: Relevance
“…54 Proton magnetic resonance spectroscopy ( 1 H MRS) can add information on the biochemical nature of MS related abnormalities, by quantifying several CNS metabo lites. 55 T2 hypointense areas and reduced T2* relaxation time (or its reciprocal R2*) are thought to be associated with iron deposition, which is believed to be a sign of neurodegeneration in patients with MS. 56 Application of these techniques to characterize the extent and distribution of MS related damage within focal lesions or in normal appearing white and grey matter has shown that tissue disruption in patients with progressive disease is more severe and more widely distributed than in patients with relapsing forms of MS. 57 Additionally, struc tural CNS damage has been shown to progress at different rates across the major clinical pheno types of MS. Global and regional quantitative MRI abnormalities corre late with the severity of clinical and cognitive impairment, and advanced and quantitative MRI techniques seem to be useful for predicting subsequent accumulation of clinical disability and cognitive impairment.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…54 Proton magnetic resonance spectroscopy ( 1 H MRS) can add information on the biochemical nature of MS related abnormalities, by quantifying several CNS metabo lites. 55 T2 hypointense areas and reduced T2* relaxation time (or its reciprocal R2*) are thought to be associated with iron deposition, which is believed to be a sign of neurodegeneration in patients with MS. 56 Application of these techniques to characterize the extent and distribution of MS related damage within focal lesions or in normal appearing white and grey matter has shown that tissue disruption in patients with progressive disease is more severe and more widely distributed than in patients with relapsing forms of MS. 57 Additionally, struc tural CNS damage has been shown to progress at different rates across the major clinical pheno types of MS. Global and regional quantitative MRI abnormalities corre late with the severity of clinical and cognitive impairment, and advanced and quantitative MRI techniques seem to be useful for predicting subsequent accumulation of clinical disability and cognitive impairment.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…Magnetization transfer imaging, which can be used to quantify intact myelin, has been proposed as a biomarker for remyelination [102]. Spectroscopy can be used to detect metabolites that reflect axonal/neuronal integrity and has been used as a measure of neuroprotective effects [103] and excitotoxicity [104]. Diffusion tensor imaging can be used to monitor tract-specific changes that may be more closely linked to clinical measures [105,106] and may be particularly powerful when combined with functional measures, such as functional MRI [107].…”
Section: New Approachesmentioning
confidence: 99%
“…Применение таких методов, как позитронно-эмиссионная томография с 18-фтордезоксиглюко-зой (ПЭТ-ФДГ) [1,2], протонная магнитно-резо-нансная спектроскопия (1Н-МРС) [3][4][5][6][7][8], диффуз-но-тензорные изображения (ДТИ) [9], позволило обнаружить нарушения в тканях, не имеющих структурных изменений на традиционных МР-томограммах. ПЭТ-ФДГ позволяет оценить метабо-лические изменения в сером веществе головного мозга, указывая на снижение скорости метаболизма глюкозы в коре и подкорковых структурах, в то вре-мя как ДТИ позволяют оценить имеющиеся пора-жения структурно неизмененного белого вещества.…”
unclassified
“…Вместе с тем результаты 1H-МРС-исследований головного мозга у пациентов с РС у зарубежных ис-следовательских групп даже при сходных критериях отбора пациентов неоднородны [3,7,8]. Однако ав-торы сходятся во мнении, что эта методика способ-на выявить изменения в головном мозге, не види-мые на традиционных МР-томограммах и позволят дополнить объем и увеличить качество получаемой диагностической информации.…”
unclassified
See 1 more Smart Citation